Motor cortex relocation after complete anatomical hemispherectomy for intractable epilepsy secondary to Rasmussen's encephalitis. (4th March 2019) - Foster, Mitchell T.; Das, Kumar; May, Paul
Abstract: Background: The authors report a case with interesting clinical and radiological outcomes following complete anatomical hemispherectomy. Methods: A seven-year-old female with medically refractory epilepsy secondary to Rasmussen's encephalitis was treated with a complete right-sided anatomical hemispherectomy. Results: Surgical intervention provided seizure relief, and at eleven-years post-operatively she was independently mobile, with spasticity of the upper limb. She had normal intellect and was pursuing higher education. Functional MRI found re-location of left-sided motor control to the remaining left hemisphere, alongside the existing motor cortex. Conclusion: This interesting case is a good example of effective neuroplasticity; motor functionality relocated an area in the contralateral hemisphere that already contained the prerequisite cellular architecture and white matter connectivity required to control movement.